Transitional justice after clean breaks the case of Portugal - Raimundo, Filipa 1982- (Lexington Books, 2024)
"This book intricately intertwines institutional and attitudinal factors, elucidating the window of opportunity for reckoning with the past. While spotlighting Portugal as a unique case study, the book probes how the emergence of 'norm-breaking' parties along with the end of old stigmas and biases, may rekindle transitional justice debates"--
Keywords: Demokratie; Justiz; Transformation; Portugal; Transitional justice / Portugal; Democracy / Portugal; Truth commissions / Portugal; Portugal / Politics and government; Justice transitionnelle / Portugal; Portugal / Politique et gouvernement